ECOLOGICAL HYDROLOGY DYNAMICS: SUSTAINING HOUSEHOLD AND INDUSTRIAL WATER NEEDS IN BALARAJA DISTRICT, TANGERANG REGENCY, INDONESIA - windasari, shindy (Jurnal Studi Inovasi, 2026)
The more rapid development of several areas in Balaraja which is triggered by the development of industrial and housing and settlement activities as well as supporting activities, the need for clean water supply will also increase where the majority of clean water supply is carried out by utilizing ground water even though the development of ground water resources is much more complicated. and more difficult than surface water development. This research aims to in-depth analysis of water needs in the Balaraja Detailed Spatial Planning Development Area (RDTR), separating the two main sectors of use, namely household and industrial. This research uses exploratory qualitative methods. This technique is a research approach that aims to explore and understand certain phenomena or events in depth. In this method, the main focus is the concept of ecogeohydrology through geoelectric estimation to obtain an overview of the characteristics of groundwater conditions in an area, especially in the RDTR Balaraja development area, analysis of water demand forecasts and the resulting impacts based on their interrelationships. The findings of this research in geological and hydrogeological analysis show that this area lacks groundwater, with dynamic system simulations providing a picture of the water deficit associated with changes in the area of ??green open space. This research is expected to provide a comprehensive view for policy makers in managing water resources in the Balaraja RDTR area in a sustainable manner.